Standing strong in the winds of change: an analysis of a Document Delivery Service in South Korea. Issue 1 (16th February 2015) - Oh, Jung Sun; Lee, Ji Won
Abstract : Purpose: – This paper aims to review the evolution of a nation-wide Document Delivery Service in Korea over the past decade, focusing on how the service has been reconfigured to sustain and fortify its position as a central channel for accessing information in the era of abundant digital resources. Design/methodology/approach: – The impacts of policy changes and technical improvements introduced incrementally over the years on the advance of the service are analyzed. The overall statistics over the period of 14 years are first presented to show the changing trends of the service, and the transaction log of the period of nine years is analyzed in detail to examine the impact of policy implementation and technical advancement on the quantity and quality of the service. Findings: – The transaction log analysis has uncovered the two main themes or directions of changes that have contributed to its robustness. First, changes introduced to streamline the service process both on the request end (unmediated requests) and on the delivery end (electronic delivery) have brought a sizable improvement on the speed of the service. Second, efforts to incorporate various resource-sharing activities into a unified service framework have led to an enhanced efficiency of the service as well as an increase in volume. Originality/value: – The empirical data demonstrating how managerial and technological changes have contributed to sustain the value of the service can be valuable benchmarking data for other services facing the same challenges.